PEMBERDAYAAN MASYARAKAT DENGAN MENGHIDUPKAN KEGIATAN DI MESJID AMALUL MUQORROBIN DESA KEDAI DURIAN - Zailani, Zailani; Ramadhani, Tazkiyah (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
The theme of the KKN this time was the role oh Muhammadiyah in public edication. so the author designed several special programs related to the theme. namely focusing on education. especially children’s education in order to empower children in dusun vii, durian shop village which was held at the Amalul Muqorrobin mosque and MDTA Amalul Muqorrobin. implementation of tutoring and implementation og literacy programs. from these programs, the community in hamlet VII, Kedai Durian, has a concern for education for children, especially religious education. From these activities the impact that can be obtained is the increased enthusiasm for learning. The spirit of reading children In the Kedai Durian. A marked change in attitude among Mdta children as well as children in the local community. Who attend the maghrib Kedai Durian these programs. It can be seen from the enthusiasm of the children in the Kedai Durian that is very high.